Peculiarities of teaching drawing and painting at Design education - Бердышев, Владимир; Захаров, Николай; Кучеровская, Вероника (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
The essay is dedicated to the problems of teaching drawing and painting at Design faculties of high schools and universities. Understanding of form elicitation patterns or image creation principles contributes to a more precise choice of figurative instruments and allows developing students’ creative abilities as required by the specifics of their professional education. The emphasis is made on the methods of space presentation and its picturesque and figurative organization. When teaching drawing and painting it is necessary to carry out an analysis of decorativeness expressed via a set of figurative tools. Spaces, volumes, planes, colours, lines and a texture are artistic means which are also formal components of a composition. The syllabus for teaching drawing and painting should include a set of educational tasks allowing combining the academic method of spatial image presentation with decorativeness, i.e. a student’s ability to see decorative properties of the nature should facilitate solving their creative tasks of a designer.